(untitled) (BIRDEM Medical Journal, 2018)
Background: Renal transplantation is the preferred treatment for end stage renal disease. Patients undergoing renal transplant surgery have several high risk features like cardiovascular diseases, diabetes mellitus and need for haemodyalysis. Renal transplant anaesthesia requires a thorough understanding of the metabolic and systemic abnormalities in end stage renal disease, familiarity with transplant medicine and expertise in managing and optimizing these patients for the best possible outcome. The aim of this study was to find out the characteristics of patients, causes of ESRD, anaesthetic management and the impact of pre-existing diseases on intraoperative or early postoperative complications of the recipients. Methods: In this retrospective study we described our experiences of 124 cases of living transplants from November 2004 – December 2016. We reviewed their medical history and noted age, sex, blood groups, causes of ESRD and history of dialysis. Preoperative investigation and preparation, as well as details of anaesthetic management, were also recorded. Results: General anaesthesia was performed in almost 97% of patients and for the rest of them, combined epidural and general anesthesia were done. The age of the patients was in the range of 15 – 65 years, with the majority of 30 - 39 years group. The mean of surgery duration was 4.5 (±1.20SD) hours. The most significant point during surgery is keeping the mean arterial pressure > 90mm Hg. Conclusions: Preoperative patient optimization, intraoperative haemodynamic stability and postoperative care of renal transplant patients have contributed to the success of renal transplant programmed in our hospital. Birdem Med J 2018; 8(2): 167-171